Keeping antibiotics working: what One Health and nature can teach us - Linda B. Oyama; Gama Dominic; Ahmad Alhanich; Shreyoshi Tarapdar (The Biochemist, 2026)
Abstract Antibiotics have transformed modern life. They help us treat bacterial infections that were once deadly, make surgery and cancer care safer, support transplantation, protect animal health, and contribute to food production. Antimicrobials more broadly also help us manage infections across people, animals, plants, and the environment. But every time these medicines are used, microorganisms are given a chance to adapt. Over time, some bacteria, fungi, and other microbes can stop responding to the treatments that once controlled them. This is antimicrobial resistance. Because resistant microbes and resistance genes can move between humans, animals, plants, and the shared environment, antimicrobial resistance is a One Health challenge. It is a shared risk, and tackling it requires shared responsibility. This article explores how we can all contribute through stewardship, infection prevention, surveillance, and better diagnostics, which can help protect the medicines we already have. It also looks to nature for new answers, including microbiome-derived antimicrobial peptides such as Lynronnes. By working together across One Health, and by learning from nature’s own molecular toolkit, we can help keep antibiotics working for the future.